The Use of Powerpoint As An Instructional Media in Elementary Schools - Harahap, Safrina; Sustri Harida, Eka (International Journal of Educational Research Excellence (IJERE), 2026)
Instructional media is a crucial learning tool that every teacher must consider when implementing the teaching and learning process. The absence of media development in instruction can lead to monotonous and unengaging lessons, potentially causing student disinterest and reluctance to participate. Such a situation undoubtedly signifies a failure in the educational process. In facing the digital era and technological advancements, a teacher must be proficient in utilizing various multimedia for instruction. In this era, teachers should employ technology-based instructional media, such as the internet or Microsoft PowerPoint, when delivering material to students. Thus, the appropriate use of instructional media can enhance student motivation and learning effectiveness.